Analyze the Future: Cloud Computing, a New Phase in Information Technology Infrastructure Management - Kulshrestha, Vartika; Verma, Dr. Seema (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The use of cloud computing is becoming widespread, but systematic study of its managerial implications is lacking. This paper examines cloud computing in the context of other major changes in Information Technology (IT) and explores the revolutionary transformations and challenges which bring to IT management. Cloud computing has a high reliability, low cost and good availability. With the increasing use of technology in modern era, there is a growing requirement of information technology infrastructure management. Over some decades in the past, organizations have put their efforts in the development and application of information technology to collect, analyze and process the data. Various computing paradigms have been employed for the purpose and needs have emerged for enormous infrastructure. Cloud Computing is evolving as a key computing platform for sharing resources that include infrastructure, software application and business processes. Virtualization is a core technology for enabling cloud resources sharing (Liang et al. 2009). Virtualization refers to the abstracting of a form of technology away from its original environment. The benefit derives from being able to redeliver it in a virtual (or â€œlogicalâ€) form capable of the same functionality as the original, but with greater flexibility (Tata Communication White Paper 2012). This paper presents how Cloud Computing service model â€“ Infrastructure as a Service (IaaS) can be used to meet the increasing demands of the Information Technology Infrastructure Management and how Cloud Computing paradigm can prove to be future solution for such systems. With IaaS, IT services can be delivered as a subscription service, eliminating up-front costs and driving down ongoing support costs.